FROM PRINCESS TO VILLAIN: A MONOMYTHIC ANALYSIS OF SOPHIE'S TRANSFORMATION IN CHAINANI'S THE SCHOOL FOR GOOD AND EVIL - Putri, Nadhilah Ghassani (Universitas Negeri Surabaya, 2026)
This article examines the narrative arc of Sophie, a central character in Soman Chainani's The School for Good and Evil (2013), by mapping her transformation into a villain through the lens of Joseph Campbell's Hero's Journey framework, also known as the Monomyth. Though traditionally reserved for protagonists, this model is applied here to explore how Sophie's development mirrors the structural path of a hero. Through close literary analysis of the novel, this study identifies thirteen out of Campbell's seventeen hero's journey stages reflected in Sophie's journey. These stages include the Call to Adventure, Refusal of the Call, Crossing the First Threshold, Belly of the Whale, Road of Trials, Meeting with the Goddess, Woman as Temptress, Atonement with the Father, Apotheosis, the Ultimate Boon, Magic Flight, Rescue from Without, and Crossing the Return Threshold. The analysis reveals that Sophie's arc is not merely a descent into evil but a transformative process that reconfigures the conventional hero-villain dynamic. Unlike the static villain figures often portrayed in traditional fantasy narratives, Sophie undergoes a complex emotional and psychological transformation shaped by rejection, internal conflict, and ultimately self-awareness. Her journey demonstrates that antagonists, like heroes, can experience meaningful character development structured around recognizable narrative patterns. This reframing invites a broader reconsideration of character roles in fantasy narratives, highlighting how antagonists, too, may undergo meaningful growth that parallels heroic transformation while ultimately serving different thematic functions.